Functional Evaluation and Genetic Landscape of Children and Young Adults Referred for Assessment of Bronchiectasis - Chau, Jeffrey Fong Ting; Lee, Mianne; Chui, Martin Man Chun; Yu, Mullin Ho Chung; Fung, Jasmine Lee Fong; Mak, Christopher Chun Yu; Chau, Christy Shuk-Kuen; Siu, Ka Ka; Hung, Jacqueline; Yeung, Kit San; Kwong, Anna Ka Yee; O'Callaghan, Christopher; et al. (Frontiers in Genetics, 2022)
Bronchiectasis is the abnormal dilation of the airway which may be caused by various etiologies in children. Beyond the more recognized cause of bacterial and viral infections and primary immunodeficiencies, other genetic conditions such as cystic fibrosis and primary ciliary dyskinesia (PCD) can also contribute to the disease. Currently, there is still debate on whether genome sequencing (GS) or exome sequencing reanalysis (rES) would be beneficial if the initial targeted testing results returned negative. This study aims to provide a back-to-back comparison between rES and GS to explore the best integrated approach for the functional and genetics evaluation for patients referred for assessment of bronchiectasis. In phase 1, an initial 60 patients were analyzed by exome sequencing (ES) with one additional individual recruited later as an affected sibling for ES. Functional evaluation of the nasal nitric oxide test, transmission electron microscopy, and high-speed video microscopy were also conducted when possible. In phase 2, GS was performed on 30 selected cases with trio samples available. To provide a back-to-back comparison, two teams of genome analysts were alternatively allocated to GS or rES and were blinded to each other’s analysis. The time for bioinformatics, analysis, and diagnostic utility was recorded for evaluation. ES revealed five positive diagnoses (5/60, 8.3%) in phase 1, and four additional diagnoses were made by rES and GS (4/30, 13%) during phase 2. Subsequently, one additional positive diagnosis was identified in a sibling by ES and an overall diagnostic yield of 10/61 (16.4%) was reached. Among those patients with a clinical suspicion of PCD (n = 31/61), the diagnostic yield was 26% (n = 8/31). While GS did not increase the diagnostic yield, we showed that a variant of uncertain significance could only be detected by GS due to improved coverage over ES and hence is a potential benefit for GS in the future. We show that genetic testing is an essential component for the diagnosis of early-onset bronchiectasis and is most effective when used in combination with functional tools such as TEM or HSVM. Our comparison of rES vs. GS suggests that rES and GS are comparable in clinical diagnosis.